Pengaruh Tekanan Kempa, Jenis Kombinasi Kayu dan Interaksinya Terhadap Kualitas Mutu Papan Laminasi - Wulandari, Febriana; Fahrussiam, Fauzan (PERENNIAL, 2024)
Lamination technology is an effort to overcome various problems resulting from the wood industry experiencing difficulties in finding raw materials to support its operations. Developing environmentally friendly materials such as laminate products is also becoming a concern in the construction sector. This research will use fast-growing wood species with bamboo, namely rajumas wood, sengon wood, and petung bamboo. Several factors, including the type of wood, type of adhesive, adhesive melt weight, and compression pressure, influence the manufacture of laminated boards. This research aims to see the effect of the type of wood combination (sengon and rajumas) with petung bamboo and the effect of pressure and their interactions on their physical and mechanical properties. The experimental design was a factorial design with 2 factors (compression pressure and combination type) with four treatments and three replications. Based on the results of testing laminated boards' physical and mechanical properties, several conclusions can be drawn, such as density testing, which shows that the type of wood combination has a significant effect. At the same time, compression pressure and its interactions have no significant effect. Moisture content testing showed that pressure had a significant effect, while the type of wood combination and its interactions had no significant effect. The thickness expansion test shows that the type of wood combination and its interactions have a significant effect, while the compression pressure has no significant effect. Thickness shrinkage testing shows that the type of wood combination, compression pressure, and their interactions do not significantly affect it. Modulus of Elasticity (MoE) testing shows that the type of wood combination, compression pressure, and their interactions do not significantly affect it. Modulus of Rupture (MoR) shows that the type of combination has a significant effect, while the compression pressure and its interaction have no significant effect.